Digital Transformation in Small and Medium Enterprise Management in the Archipelago: Challenges and Opportunities - Fadhilah, Nurul (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2025)
Digital transformation has become an urgent need for Small and Medium Enterprises (SMEs) in the archipelago to remain competitive and thrive in the era of globalization. This article explores the challenges and opportunities faced by Indonesian SMEs in the digital transformation process. Based on case studies and interviews with industry players, we identify several key challenges, including resource constraints, lack of digital skills, and infrastructure barriers. On the other hand, emerging opportunities include access to wider markets, increased operational efficiency, and the ability to innovate. These findings suggest that while digital transformation offers significant benefits, SMEs must face various obstacles that require strategic solutions and support from various parties, including the government and financial institutions. This article offers practical recommendations to facilitate the adoption of digital technologies among SMEs and contribute to the development of more effective strategies to capitalize on existing opportunities.